Assessment of low-input technologies to improve productivity of early harvested cassava in Côte d'Ivoire. Issue 9 (20th October 2016) - Gnahoua, Jean-Baptiste Gnélié; Ettien, Djétchi Jean Baptiste; N'zué, Boni; De Neve, Stefaan; Boeckx, Pascal
ABSTRACT: In Côte d'Ivoire, smallholder farmers cultivate cassava on poor, highly weathered soils without improved varieties or fertilizer inputs. Land pressure combined with high demand result in premature harvests and low yields. Furthermore, subsistence agriculture limits the adoption of input-intensive technologies. This study aimed at identifying integrated soil fertility management systems for increasing cassava productivity and profitability in two locations in southern Côte d'Ivoire. The integrated technical interventions included improved cassava genotypes and modified spacing, legume intercropping, and application of fertilizer at moderate doses. Overall, an improved cassava variety (Yavo) generally out-yielded the other varieties at both sites. Legumes performed better at the higher soil fertility site and gave higher grain yield and biological nitrogen fixation in a 2 × 0.5 m cassava spacing compared to 1 × 1 m. The response of cassava to nutrient amendments varied between sites, suggesting the need for site-specific adaptations. Fertilizer application was essential to avoid cassava yield reduction upon legume intercropping as a result of competition for nutrients and N immobilization and delayed re-mineralization of legume residues. Growing legumes, however, substantially increased profitability. Hence, better synchronization of legume sowing, legume residue and fertilizer application in relation to cassava growth phases is needed.